Efektivitas Konseling Person-Centered untuk Meningkatkan Self-Esteem Remaja yang Mengalami Penghinaan Verbal Orang Tua - Muhammad Rivai; Aisyah Suryani; Suparman; Muliyadi; Ahmad Kamil (Mataram University, 2026)
Parental verbal insults can negatively affect adolescents' psychological development, particularly self-esteem. Repeated exposure to negative labeling, degrading comparisons, and other demeaning verbal expressions may lead adolescents to develop a negative self-concept and low self-confidence. This study aimed to examine the effectiveness of Person-Centered Therapy in improving the self-esteem of adolescents who experience parental verbal insults. This study employed a Pretest-Posttest Case Series design. The population consisted of 10 adolescents aged 15–20 years living in Dusun Buasan, Pana Village, Alla District, Enrekang Regency. Based on screening using the Rosenberg Self-esteem Scale (RSES), two participants with low self-esteem and repeated experiences of parental verbal insults were selected. The intervention was conducted through six individual counseling sessions. Data were collected using the RSES, observations, and interviews and analyzed descriptively. The findings showed that both participants experienced increased self-esteem after the intervention. The first participant's score increased from 12 to 22 (83.3%), while the second participant's score increased from 14 to 21 (50%). Positive behavioral changes were also observed, including increased self-confidence, self-acceptance, and social interaction. These findings indicate that Person-Centered Therapy can help adolescents develop a more positive self-concept following experiences of parental verbal insults.